Social System and Impact of Modernization of Fishing Technology among Bugis Fishermen in Kemujan Village, Karimunjawa District, Jepara Regency 1979-2001 - Nugraha, Febrian Aditya; Utama, Mahendra Pudji (Diponegoro University, 2023)
Bugis fishermen as residents of Kemujan Village came through migration. They have traditional knowledge in the fishing system by utilizing simple equipment. Before 1960, they still caught fish using sailboats. Using historical methods, this study analyzes changes in the modern equipment system after the modernization of fishing gear and changes in fishing orientation leading to large-scale fishing. This study also aims to describe the impact of changes in orientation and modernization of fishing gear for Bugis fishermen in Kemujan. The changes were based on the revolutionary policies of the New Order Government. Fishermen gradually used boats with outboard engines. Then, the existence of Global Positioning System (GPS) technology and fish finders influenced the ease of fishermen to catch fish at sea. However, in practice there is a gap in the fishing community because not all fishermen can access these new economic sources. The results of the study show that there is a reduction in income because government assistance often does not reach ordinary fishermen but can only be accessed by the juragan.